Contour generation algorithm for Projection Mask Stereolithography 3D printing process - Faeiz Azizi, Adnan; F. R. M., Romlay (2018)
Projection mask stereolithography is a latest technology in 3D printing industry. It relies on UV projection to cure the photocurable resin layer-by-layer to build the solid 3D object. The projections are generated from tessellated STL CAD model using contour generation algorithm that generates 2D contours as the projection mask. The computational of the algorithm consumes a lot of memory for high-resolution printing. Low-resolution causes the stair-case effect to visibly appear on the printed model. Using real-time contour generation algorithm reduces the memory consumption and retains the high-resolution printing quality and accuracy. Pixel line mapping algorithm is implemented on the generated line segments to scale the line segments with respect to the display resolution of the projection device. Contour loop algorithm connects each of these pixel line segments into multiple closed-loop contours. The algorithms are implemented on an Alien STL model having 150350 facets. It is found that the pixel mapping algorithm correctly scales the model while retaining the aspect ratio of the model. The result of contour loop algorithm shows that the mean contour loop execution time is 0.87 milliseconds which is relevant for real-time application.